2015
DOI: 10.31478/201502c
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Community Health Workers into the Mainstream of U.S. Health Care

Abstract: We have an innovation that is showing tremendous gains in improving health, especially among vulnerable populations. It has produced a return on investment of 4:1 when applied to children with asthma and a return on investment of 3:1 for Medicaid enrollees with unmet longterm care needs (Felix et al., 2011). Among participating patients with HIV, 60 percent achieve undetectable viral loads (Behforouz, 2014). In fact, examples keep emerging from around the country about its effectiveness in improving health out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…Study findings suggest that additional efforts should focus on WLH who have adequate access to care to ensure that the innovation of the Pap is not merely realized by some, but all WLH. Utilizing community health workers to promote cervical cancer screening and continued health services utilization for WLH should prove most effective [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Study findings suggest that additional efforts should focus on WLH who have adequate access to care to ensure that the innovation of the Pap is not merely realized by some, but all WLH. Utilizing community health workers to promote cervical cancer screening and continued health services utilization for WLH should prove most effective [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Reports from the Institute of Medicine (2015) and the Agency for Healthcare Research and Quality (2009) have recommended expanded use of CHWs as a vital strategy to improve health behaviors and more effectively link vulnerable people to healthcare [31,32]. In addition, previous studies have demonstrated that authentic healing relationships improve outcomes among patients with comorbid chronic conditions [9].…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges of growing a CHW workforce relates to sustainable funding mechanisms where CHW positions are primarily supported through grants, which are time-limited and often not sustained [19]. Our sample of employer respondents reported a combination of funding sources, with a notable three-quarters of CHW employers utilizing agency operating budgets, presumably with some combination of either government funds, private funds, feefor-service or other funding mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Though these examples offer guidance to the other states that do not have a comprehensive CHW program, including Nebraska, the challenge is determining how exactly these policy recommendations should be implemented, and this is where specific context and nuance need to be considered and studied, such as place of employment, geographic location (i.e., rural, suburban,urban), and amount of organizational and community resources. For example, the California Health Workforce Alliance conducted a statewide assessment that identified several obstacles to bringing CHWs into the mainstream of U.S. healthcare, including limited professional recognition; lack of data to make the business case; sustainability; and lack of knowledge of best practices [19]. Adding to this complexity is the number of national trends in public health such as implementation of the Patient Protection and Affordable Care Act (ACA), Health in All Policies, evidence-based public health practice, and primary care and public health integration.…”
Section: Introductionmentioning
confidence: 99%